Autism Spectrum disorders (ASD) in South Asia: a systematic review - Hossain, Mohammad Didar; Ahmed, Helal Uddin; Jalal Uddin, M. M.; Chowdhury, Waziul Alam; Iqbal, Mohammad Shamim; Kabir, Razin Iqbal; Chowdhury, Imran Ahmed; Aftab, Afzal; Datta, Pran Gopal; Rabbani, Golam; Hossain, Saima Wazed; Sarker, Malabika (© 2017 BioMed Central Ltd., 2018)
This article was published in the BMC Psychiatry [© 2017 The Author(s)] and the definitive version is available at : https://doi.org/10.1186/s12888-017-1440-x The Journal's website is at https://bmcpsychiatry.biomedcentral.com/articles/10.1186/s12888-017-1440-x